STRATEGI PENGEMBANGAN PROFESIONAL GURU INDIVIDU BERKEBUTUHAN KHUSUS DALAM PENGELOLAAN KELAS EKSKLUSIF (STUDI KASUS SEKOLAH TALENTA CENTER BEKASI JAWA BARAT) - Paryani Agustini; Imas Masriah; Sri Utaminingsih (STKIP Pesisir Selatan, 2026)
This study aims to analyze professional development strategies for teachers of students with special needs (IBK) in managing exclusive classrooms from an educational management perspective. The background of this study is the increasing demand for professional teachers who are capable of managing exclusive classrooms effectively while responding to the diverse needs of IBK. Many schools still face challenges related to limited teacher competencies, fragmented professional development programs, and the absence of a systematic management framework. This research employed a qualitative case study design conducted at Talenta Center School, Bekasi. Data were collected through in-depth interviews, classroom observations, and document analysis involving school leaders and IBK teachers. The findings reveal that professional development is effectively implemented through needs-based training, continuous mentoring, collaborative reflection, and experiential learning supported by school management. These strategies contribute to improvements in pedagogical competence, classroom management skills, and professional attitudes of IBK teachers. This study highlights the importance of structured and sustainable professional development programs integrated into school management systems.